Peningkatan Kompetensi Guru melalui Penyediaan Sumber Belajar Berkualitas di Desa Margajaya - Handayani Handayani; Rahma Widiantie; Agus Prianto; Nur Hasanah; Lela Siti Thohiryah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
The role of teachers is crucial in enhancing the competence and quality of learning in schools. The lack of learning resources, such as books and the unavailability of libraries, hinders teachers from accessing quality learning materials, which impacts the effectiveness of their teaching. Community service activities were conducted to address these challenges by providing books for teachers and establishing reading corners. This initiative aims to improve teachers' competencies to achieve quality learning and increase students' reading interest at SDN 1 Margajaya. The implementation of the activities involved interviews and observations with the teachers at SDN Margajaya. The community service resulted in the successful procurement of books for teachers, which enhances their knowledge and competencies for delivering higher-quality education. Another outcome of the initiative is the establishment of a reading corner that accommodates students' needs for accessing reading materials, thereby increasing their interest in reading. As a result, students' understanding of the importance of reading for expanding their knowledge has significantly improved.